So i have got to the point where the problem looks like this. -4/6x-3=3/6x+2

3y= -2x-9.................................first equation

y= 1/2x +2

Using substitution method

the value of y in the second equation will be substituted in the firstequation

3(1/2x+2)= -2x-9

3/2x+6= -2x-9

3/2x+2x= -6-9

3 1/2x= -15

7/2x= -15

x= -15*2/7

x= -30/7= -4 2/7

y= 1/2(-30/7+2)

y= -60/7+1

y= -8 4/7+1

y= -7 4/7

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up